Resonance modes of voltage-modulated Scanning Force Microscopy - Labardi, M.; V. Likodimos; Allegrini, M. (Applied Physics A: Materials Science and Processing, 2001)
Mechanical resonance modes of the scanning force microscope (SFM) cantilever in contact conditions provide contrast enhancement in the imaging of surface charges when using voltage modulation techniques tuned to such resonances. Extensions of the method were made as regards the lateral (twisting) and frontal (buckling) modes of the cantilever, as well as the enhanced second harmonic detection of voltage-modulated response at resonance and near-resonance detection in the SFM tapping mode. As an example of application, vibration spectra and images taken on a triglycine sulfate (TGS) single crystal are discussed. © Springer-Verlag 2001.